Application of the Project Based Learning (PJBL) Learning Model to Increase Student Activity and Learning Outcomes - Ramadhan, Mustafa (Jurnal Guru Komputer, 2021)
The aims of the research were to find out (1) to increase the activeness of studying the database for class XII RPL students at SMK N 4 Bandung using the project-based learning (pjbl) learning model (2) to increase the learning outcomes for class XII RPL students at SMK N 4 Bandung using the learning model PJBL This research is a type of classroom action research with a model developed by Kemmis and Mc. Taggart. The research subjects were students of class XII RPL Software Engineering Expertise Program (RPL) SMK Negeri 4 Bandung, with a total of 29 students. This study consisted of 2 (two) cycles where there were two meetings in each cycle. The data analysis technique uses descriptive qualitative analysis. The research success criteria set for student learning activeness is 75.00% of students are actively involved both physically, mentally, and socially in the process of learning activities and for student learning outcomes is 75 for a rating scale of 1-100. The results showed that the application of the PJBL learning model could increase the activity and learning outcomes of class XII RPL students at SMK Negeri 4 Bandung. The average learning activity of XII RPL students in the pre-cycle only reached 35.33%. After applying the PJBL learning model in cycle I, the average student learning activity increased to 60.13% and in cycle II it increased to 81.02%. Based on these results, the hypothesis in the study was accepted.